2021
DOI: 10.1007/s11694-021-01217-w
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of nano-ZnO and Mentha piperita essential oil on the moisture sorption isotherm, antibacterial activity, physicochemical, mechanical, and barrier properties of gelatin film

Abstract: This study aimed to evaluate the synergistic effect of nano-ZnO (ZnO-N) and Mentha piperita essential oil (MEO) on the functional and antibacterial properties of bovine gelatin bionanocomposite film. A mixture of ZnO-N (1%, 3%, and 5%) and MEO (1%, 2%, and 3%) was incorporated into gelatin films. The physicochemical, mechanical, antimicrobial, and barrier properties of the films were explored. Results demonstrated that adding combined ZnO-N and MEO to films lead to decreased moisture content, solubility, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Consequently, the highest total color difference (ΔE) was observed after blending the G/PVA mixture with BCCE and ZnONPs (ΔE = 7.9). Javidi et al [ 43 ] also reported a decrease in the lightness of gelatin nanocomposites owing to the presence of ZnONPs and Mentha piperita extract. Similar observations of color changes were described by Shahvalizadeh et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the highest total color difference (ΔE) was observed after blending the G/PVA mixture with BCCE and ZnONPs (ΔE = 7.9). Javidi et al [ 43 ] also reported a decrease in the lightness of gelatin nanocomposites owing to the presence of ZnONPs and Mentha piperita extract. Similar observations of color changes were described by Shahvalizadeh et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The color indices measured included the lightness intensity or L * (white = 100 and black = 0), the redness–greenness intensity or a * (green = −80 and red = 100), and the yellowness–blueness intensity or b * (blue = −80 and yellow = 70). [ 51 ]…”
Section: Methodsmentioning
confidence: 99%
“…The color indices measured included the lightness intensity or L* (white = 100 and black = 0), the redness-greenness intensity or a* (green = −80 and red = 100), and the yellowness-blueness intensity or b* (blue = −80 and yellow = 70). [51] Determination of Film Transparency and UV-vis Spectra: The UV-vis light transmittance of film samples at the wavelength of 200-1100 nm was measured using a spectrophotometer (Shimadzu, model UV-1700, Japan). A transparent glass plate was used as reference.…”
Section: Measurement Of Water Vapor (Wvp) and Oxygen (Op) Permeabilit...mentioning
confidence: 99%
“…In recent years, some researchers have shown the synergistic effect of NPs with each other and with other improver compounds in polymers matrices [19,20]. However, the synergistic effects of polyphenols and nanofiller incorporation in the polymer have been scarcely studied [16].…”
Section: Introductionmentioning
confidence: 99%